The freedom to learn-independent campus curriculum for shielded metal arc welding: A teaching module development - Butar, David Beckham Butar; Erizon, Nelvi; Karudin, Arwizet; Primawati, Primawati (Jurnal Pendidikan Teknologi Kejuruan, 2024)
This study was triggered by the existing teaching modules for the Shielded Metal Arc Welding (SMAW) subjects taught at vocational high schools, which do not align with the Freedom to Learn-Independent Campus (FLIC) learning objectives, and do not provide a systematic organization. In order to enhance the learning experience, this research developed a new learning module that integrated Problem-based Learning (PBL), promoting critical thinking, and the practical application of theoretical concepts, following the FLIC curriculum. Utilizing a Research and Development (R&D) approach with the Instructional Design Institute (IDI) model, this study involved two welding instructors and four lecturers as validators to assess the content and usability of the module. The IDI model comprised three steps: instructional (define), development (develop), and institute (evaluate). The research findings regarding the validity assessment by subject matter experts yielded a final validity score of 0.924, while media and language experts provided a score of 0.936, meeting the valid criteria. The practical usability test of the learning module resulted in a score of 94%, indicating that it is highly practical for students to use as learning media. Based on the validity and practicality assessments of the developed module, it can be concluded that the SMAW learning module is highly practical to use as teaching media, aligning with FLIC curriculum.